PENINGKATAN WAWASAN BUDAYA LOKAL MELALUI METODE PROBLEM BASED LEARNING DALAM PENDIDIKAN PANCASILA - Anikotul Meliana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Pancasila Education plays an important role in developing students' insight into local culture; however, preliminary observation in class VII-D of SMPN 4 Madiun showed that students' insight into local culture was still relatively low due to teacher-centered learning. This study aims to examine the extent to which the application of the Problem Based Learning (PBL) method through group work themed around local culture can improve students' insight into local culture in Pancasila Education. The study used a Classroom Action Research approach based on the Kemmis and McTaggart model, carried out through four stages in each cycle: planning, action, observation, and reflection, involving 31 students of class VII-D of SMPN 4 Madiun, divided into five heterogeneous groups themed around Indonesian archipelago cultures. Data were collected through participatory observation, performance assessment, and documentation using a five-aspect assessment rubric. The results showed a class average score of 91.77 with 100% classical learning mastery among the 31 students. The highest scores were achieved in the aspects of local culture identification and presentation skills (4.00 each), while the lowest score was in the aspect of respecting culture (3.23). These findings indicate that applying PBL through group work themed around local culture is effective in improving students' local cultural insight, although mutual respect for culture between groups still needs to be strengthened in the following cycle.